2008
DOI: 10.1590/s1679-62252008000400011
|View full text |Cite
|
Sign up to set email alerts
|

Alterations on piscivorous diet following change in abundance of prey after impoundment in a Neotropical river

Abstract: The goal of this study was to investigate the alterations of diet of a piscivorous fish (Acestrorhynchus pantaneiro) following changes in abundance of a forage fish (Moenkhausia dichroura) during the trophic upsurge stage in a reservoir. Fish samplings were taken monthly in the Manso Reservoir (State of Mato Grosso, Brazil) from March 2000 to February 2001 (period I) and from March 2003 to February 2004 (period II). The abundance of Moenkhausia dichroura in the reservoir was significantly different in both per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…In the upper Paraná River floodplain, fish was the main food for P. squamosissimus, and shrimp complemented its diet , whereas in Amazon region, shrimp dominated the diet of this species, and fish was a secondary food (Goulding & Ferreira, 1984). The wide food spectrum of P. ternetzi represented the pattern commonly verified for piscivorous species (Almeida et al, 1997;L'abeé-Lund, 2002;Hahn et al, 1997;Cantanhêde et al, 2008), however, corroborating Popova (1978), the basic part of the diet of P. ternetzi has included few species.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the upper Paraná River floodplain, fish was the main food for P. squamosissimus, and shrimp complemented its diet , whereas in Amazon region, shrimp dominated the diet of this species, and fish was a secondary food (Goulding & Ferreira, 1984). The wide food spectrum of P. ternetzi represented the pattern commonly verified for piscivorous species (Almeida et al, 1997;L'abeé-Lund, 2002;Hahn et al, 1997;Cantanhêde et al, 2008), however, corroborating Popova (1978), the basic part of the diet of P. ternetzi has included few species.…”
Section: Discussionsupporting
confidence: 58%
“…The composition, abundance and availability of prey species affect the diet of predators (Cantanhêde et al, 2008(Cantanhêde et al, , 2009Meurer & Zaniboni-Filho, 2012) as well predators can also exert strong control on prey community (Carpenter & Kitchell, 1993). Although the availability of prey had been considered the primary factor in food intake by fish, other factors as type and size of the prey, place of refuge, and activity of predator and prey are also important for the item selection (Kahilainen & Lehtonen, 2003;Cantanhêde et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Meurer, ZaniboniFilho (2012) and Cantanhêde et al (2008) observed that A. pantaneiro shows opportunistic behavior, feeding on the most abundant species in the environment. In the upper Uruguay River, the species A. fasciatus and S. brevipinna are extremely abundant in the Itá and Machadinho reservoirs, 9 e160084 [9] and in this study they showed an increase in the abundance of juveniles during fuller reservoir conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found an importance of piscivore fish, with H. malabaricus and A. pantaneiro combined, the second and third largest catches respectively in terms of biomass. The capacity of both to adapt their feeding according to the most abundant prey in the reservoirs (Cantanhede et al, 2008;Pompeu and Godinho, 2001;Novakowski et al, 2007), certainly favored the maintenance of these species under different conditions. Added to the adaptive qualities of the A. pantaneiro, portioned spawning with relatively high fertilization and an absence of parental care (Meurer and Zaniboni-Filho, 2012).…”
Section: Discussionmentioning
confidence: 99%